2004
DOI: 10.1007/s10295-004-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of hexachlorocyclohexane in soil during solid-phase bioremediation

Abstract: Soil containing hexachlorocyclohexane (HCH) was spiked with (14)C-gamma-HCH and then subjected to bioremediation in bench-scale microcosms to determine the rate and extent of mineralization of the (14)C-labeled HCH to (14)CO(2). The soil was treated using two different DARAMEND amendments, D6386 and D6390. The amendments were previously found to enhance natural HCH bioremediation as determined by measuring the disappearance of parent compounds under either strictly oxic conditions (D6386), or cycled anoxic/oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Phillips et al (2004) reported that negligible mineralization of 14 C-c-HCH occurred in soil microcosms where highly anoxic conditions were alternated with aeration and oxic conditions. In contrast, considerable mineralization (47% recovery of 14 CO 2 ) was detected in strictly oxic microcosms after 80 days incubation (Table 2).…”
Section: Physical Properties and Persistence Of Hchsmentioning
confidence: 98%
“…Phillips et al (2004) reported that negligible mineralization of 14 C-c-HCH occurred in soil microcosms where highly anoxic conditions were alternated with aeration and oxic conditions. In contrast, considerable mineralization (47% recovery of 14 CO 2 ) was detected in strictly oxic microcosms after 80 days incubation (Table 2).…”
Section: Physical Properties and Persistence Of Hchsmentioning
confidence: 98%
“…[78][79][80][81][82][83][84][85][86][87][88][89] In general, the HCH isomers can be biodegraded to a series of less chlorinated organic compounds under aerobic and anaerobic conditions, and in some cases can be used as the sole carbon source for bacterial growth. 64,72,78 In the following paragraphs, the highlights from several representative studies on the anaerobic and aerobic biotransformation of HCHs are presented. In 1972, Tsukano and Kobayashi 24 studied the degradation of lindane in flooded rice field soils.…”
Section: Biotic Pathwaysmentioning
confidence: 99%
“…[60][61][62][63] Researchers showed that soil microorganisms could degrade HCH isomers under certain conditions and moderate pH. [64][65][66][67][68][69][70][71][72][73][74] Furthermore, enhanced HCH degradation could be achieved when key environmental factors were optimized. [73][74][75][76][77] In 2006, the first full-scale in situ bioremediation of HCHs had been reported by Philips et al 74 Over the last few years, the focus of biologically mediated HCH transformations by specific bacterial strains has been on the genetic aspects and at the molecular level.…”
Section: Biotic Pathwaysmentioning
confidence: 99%
“…Phillips et al (135) used proprietary biostimulation agents known as Daramend products derived from natural plant fibers to treat 1,100 tons of soil contaminated with high HCH concentrations (ϳ5,000 mg kg Ϫ1 ) in the United States. Based on developmental work in laboratory microcosms (134), two Daramend treatment approaches (cycled anaerobic/aerobic treatment and a strictly aerobic treatment) using two different Daramend products (D6390 and D6386, respectively) were used. Some tillage to enhance aerobic degradation was also used, and reductions averaging just under 50% were achieved over a year of treatment.…”
Section: Vol 74 2010 Microbial Degradation Of Hch 71mentioning
confidence: 99%